Gestational Weight Gain and Perinatal Outcomes by Pre-Pregnancy Obesity Class [1OP]. Issue 1 (May 2017) - Wilkins, Emilia; Alabaster, Amy; Gunderson, Erica
Abstract : INTRODUCTION: Gestational weight gain (GWG) is a modifiable risk factor that could mitigate poor perinatal outcomes for obese women. This study evaluated the risk of adverse perinatal outcomes among obese women that fall below the Institute of Medicine (IOM) guidelines for GWG. METHODS: This retrospective cohort study included 19, 810 obese women delivering singleton, live births, greater than 35 weeks in 2009-2012 at Kaiser Permanente Northern California hospitals. Logistic regression was used to estimate the odds ratios (OR, 95% CI) of newborn [size for gestational age, NICU admission, length of hospital stay (LOS)] and maternal (mode of delivery, preeclampsia, gestational hypertension) outcomes associated with GWG below IOM guidelines (less than −2kg, -2kg – 2kg, or 2kg – 5kg) compared to within IOM guidelines (5kg-9kg) for pre-pregnancy obesity classes 1 to 3. Models were adjusted for socio-demographics, parity, gestational age, prenatal care, diabetes, hypertension and smoking. RESULTS: Among class 3 obese women, GWG below -2 kg compared to GWG within IOM guidelines was associated with lower odds of: large for gestational age infants OR=0.44 (0.27 – 0.71), preeclampsia/eclampsia OR=0.51 (0.26 – 0.93), cesarean section OR=0.50 (0.35 – 0.71), NICU admission OR 0.70 (0.45 – 1.08) and LOS greater than 3 days OR=0.53 (0.28 – 0.76), but higher odds of small for gestational age OR=2.61 (1.11 – 6.20). Findings were similar for other obesity classes. CONCLUSION: Weight loss among severely obese women is associated with improved perinatal outcomes, and higher risk of small for gestational age infants, but without the increased risk of other poor neonatal outcomes.